The implications of NVC in the classroom/Ng Kui Choo - Ng, Kui Choo (Institut Teknologi MARA Cawangan Sarawak, 1991)
In the process of classroom teaching, the teacher is in part communicating knowledge, in part communicating the nonverbal aspects of social skills to the student. Content aside, we see ourselves as excellent communicators, but there often exists an unwitting chasm between how we perceive ourselves and how the student perceives us. Fontana (1981) sees the teacher and his class as a distinct social unit fraught with undercurrents of social relationships and social attitudes which shape individual and group responses in subtle ways. These undercurrents are manifested in parallel attitudinal differences towards particular teachers; at best friendliness; at worse, hostility. In order to provide optimum learning environments for the student, it is imperative that the teacher comes to grips with aspects of communication skills that can serve a direct and immediate impact on the learning process.